Acid Adaptive Mechanisms of Campylobacter jejuni in the Gastrointestinal Tract - Askoura, Momen Mahmoud Ez ElArab Abd ElAziz M. (Université d'Ottawa / University of Ottawa, 2015)
Campylobacter jejuni is a prevalent cause of bacterial gastroenteritis in humans worldwide. The mechanism by which C. jejuni survives stomach acidity remains unknown. In this study, we have demonstrated that the ferric uptake regulator Fur plays an important role in Campylobacter acid survival. C. jejuni with a fur deletion was more sensitive to acid than the wild-type. Profiling the acid stimulon of the C. jejuni ∆fur mutant allowed us to uncover Fur-regulated genes under acidic conditions. The up-regulation of heat shock genes and the down-regulation of genes involved in flagellar and cell envelope biogenesis in the fur mutant highlight the importance of Fur in Campylobacter acid survival. Furthermore, prior exposure of C. jejuni to acid increased its capacity to survive other stresses, such as oxidative stress. This enhanced survival in the presence of oxidative stress was shown to be Fur-dependent through the regulation of catalase katA expression. Interestingly, Fur-mediated repression of katA was alleviated under low-pH conditions, allowing for higher catalase expression and defense against oxidative stress. Additionally, the transcriptome of C. jejuni under acidic conditions revealed that many genes involved in Campylobacter pathogenesis were differentially expressed. Prior exposure of C. jejuni to acid significantly increased its adherence to and invasion of human epithelial cells. Furthermore, in vivo experiments using Galleria mellonella larvae showed that acid exposure markedly enhanced Campylobacter virulence potential. In conclusion, this study demonstrates that the ferric uptake regulator Fur is a potential regulator of Campylobacter acid survival and cross-protection against other stresses. Moreover, our results suggest that the obligate passage of C. jejuni through the stomach acid barrier modulates the expression of its virulence factors and predisposes the bacterium for efficient gut colonization.
Keywords: Campylobacter jejuni; Acid stress